The influence of auditor independence, moral integrity on violations of audit compliance triggers attitudes - Vina Merliana (JAAF (Journal of Applied Accounting and Finance), 2023)
The purpose of this study is to evaluate the impact of auditor independence, moral integrity on violations of compliance audit trigger attitudes, because attitudes can determine a person's character to carry out an intentional or unintentional action, a person's morals come out of oneself, influenced from outside that can damage the mind. The sample size is 35 respondents. The quantitative research methodology employed in this study includes sampling utilizing the probability sampling method along with descriptive and verification approaches. The findings revealed that auditor independence has a insignificant positive effect on compliance audit violations that trigger attitudes, and the same moral integrity has a insignificant positive effect on those same violations. Auditors are professional, thus, any other immoral acts they avoid at all cost.